STOPP/START Anti-aggregation and Anticoagulation Alerts in Atrial Fibrillation - Salis, Francesco; Palimodde, Antonella; Rundeddu, Samuele; Mandas, Antonella (Current Vascular Pharmacology, 2023)
Background: Atrial Fibrillation (AF) is common in the elderly. A key component of AF management is Oral Anticoagulant Therapy (OAT), consisting of Vitamin K Antagonists (VKAs) or Direct Oral Anticoagulants (DOACs). The aim of the present study is to check, using STOPP (Screening Tool of Older Persons’ Prescriptions)/START (Screening Tool to Alert to Right Treatment) Criteria, if such drugs are potentially inappropriately prescribed/omitted in an elderly population with AF, and to determine their impact on mortality. Methods: This study included patients (n = 427) with nonvalvular AF consecutively evaluated between 2013 and 2019 at the Geriatric Outpatient Service, University Hospital of Monserrato, Cagliari, Italy, and followed up for 36 months. The OAT group included 330 patients; the other 97 patients constituted the non-OAT group. The sample was assessed for STOPP/START criteria. Results: We found no difference (p > 0.1) in comorbidity burden, frailty, and cardio-cerebro-vascular disease prevalence in the two groups, which also did not present a difference in 36-month mortality (p = 0.97). OAT was overall appropriately taken, and 62.4% of OAT-group presented the START criterion to take antiplatelets but also the STOPP criterion not to take them, because of the simultaneous anticoagulant intake. In the non-OAT group, 69.1% presented the START criterion to take anticoagulants, and 21.6% the START criterion to take antiplatelets. Conclusion: Patients with AF are often prone to under or over-prescription, particularly of antithrombotic drugs. The STOPP/START criteria are a valid tool to assess and correct wrong therapeutic choices. In frail and comorbid subjects, survival is not correlated with the assumption of OAT.
Keywords: Atrial fibrillation